Analisis Perbandingan Performa Codec H.264 & H.265 Video Streaming Dari Segi Quality of Service - Indra Saputra; Harun Mukhtar; Januar Al Amien (Universitas Muhammadiyah Riau, 2021)
Video streaming is a technology that is often used when watching videos on the internet without having to download then video to play it. Some problems that affect the performance of video streaming are such as the large capacity of the video size, the capacity of the video size affects the smoothness when streaming video. In this research, two video compression methods will be compared, namely H.264 codec and H.265 codec. The test is carried out to determine the effect of using the compression method according to changes in the codec ang framerate used. After testing the two codec, it can be concluded that the H.265 codec is more effective to apply than the H.264 codec.